2010
DOI: 10.4161/mabs.2.3.11416
|View full text |Cite
|
Sign up to set email alerts
|

Potent and broad neutralizing activity of a single chain antibody fragment against cell-free and cell-associated HIV-1

Abstract: (2010) Potent and broad neutralizing activity of a single chain antibody fragment against cell-free and cellassociated HIV-1, mAbs, 2:3, 266-274,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…For example, antibodies can block infection by free virions, but they can also direct the killing of infected cells that express cell surface gp160 or its fragments by antibody-dependent cell-mediated cytotoxicity/antibodydependent cell-mediated viral inhibition (ADCC/ADCVI) (40,41). In addition, antibodies may be able to block synapse formation and subsequent cell contact-mediated viral transmission (42)(43)(44). To determine whether the antibodies used in this study can interfere with cell contact-mediated transmission of HIV-1 YU2 , we compared their activity in established cell-free and cell contact-permitting transmission assays (45) in vitro (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, antibodies can block infection by free virions, but they can also direct the killing of infected cells that express cell surface gp160 or its fragments by antibody-dependent cell-mediated cytotoxicity/antibodydependent cell-mediated viral inhibition (ADCC/ADCVI) (40,41). In addition, antibodies may be able to block synapse formation and subsequent cell contact-mediated viral transmission (42)(43)(44). To determine whether the antibodies used in this study can interfere with cell contact-mediated transmission of HIV-1 YU2 , we compared their activity in established cell-free and cell contact-permitting transmission assays (45) in vitro (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For this to occur, the immune system must be presented with the target in the desired conformation and then create antibodies at an affinity that outcompetes the native function at a level that eliminates reservoirs of the pathogen. An example of this in HIV vaccines is gp120 as a target for a neutralizing antibody response (25, 26). Here, the key function of the target is binding and entrance to cells via the CD4 / gp120 interaction (27).…”
Section: Neutralization and Breadth Of The Antibody Responsementioning
confidence: 99%
“…In a recent study, Zhang et al used a sequential antigen panning (SAP) method and successfully isolated broadly cross-reactive antibodies with two-to threefold lower IC 50 s than the parent HIV-1-neutralizing antibody scFv X5 (41). Upon further characterization, they found that the highly potent m9 antibody not only exhibited broad neutralizing activity but also suppressed the generation of escape mutants upon immune selection (40). Addi-tional studies on broadly neutralizing antibodies to HIV from memory B cells also suggest that affinity has an important role in breadth and potency of neutralization (23,31).…”
Section: Discussionmentioning
confidence: 99%